Interspecific Variation in the Unsaturation Level of Seed Oils Were Associated With the Expression Pattern Shifts of Duplicated Desaturase Genes and the Potential Role of Other Regulatory Genes - Wang, Mengli; Gao, Lexuan; Li, Gengyun; Zhou, Chengchuan; Jian, Jinjing; Xing, Zhen; Wang, Yuguo; Zhang, Wenju; Song, Zhiping; Hu, Yonghong; Yang, Ji (Frontiers in Plant Science, 2021)
Seed oils are of great economic importance both for human consumption and industrial applications. The nutritional quality and industrial value of seed oils are mostly determined by their fatty acid profiles, especially the relative proportions of unsaturated fatty acids. Tree peony seed oils have recently been recognized as novel edible oils enriched in α-linolenic acid (ALA). However, congeneric species, such as Paeonia ostii and P. ludlowii, showed marked variation in the relative proportions of different unsaturated fatty acids. By comparing the dynamics of fatty acid accumulation and the time-course gene expression patterns between P. ostii and P. ludlowii, we identified seed-specific genes that were differentially expressed between two species in developing seeds, and showed congruent patterns of variation between expression levels and phenotypes. In addition to the well-known desaturase and acyltransferase genes associated with fatty acid desaturation, among them were some genes that were conservatively co-expressed with the desaturation pathway genes across phylogenetically distant ALA-rich species, including Camelina sativa and Perilla frutescens. Go enrichment analysis revealed that these genes were majorly involved in transcriptional regulation, protein post-translational modification and hormone biosynthesis and response, suggesting that the fatty acid synthesis and desaturation pathway might be subject to multiple levels of regulation.